Computation of stability derivatives of an oscillating cone for specific heat ratio = 1.66 - Shabana, Aysha; Monis, Renita Sharon; Crasta, Asha; Khan, Sher Afghan (Institute of Physics Publishing, 2018)
In this paper the expressions for stiffness and Damping derivatives are obtained in a closed form for perfect gas where the flow is quasi-steady and axi-axisymmetric, and the nose semi angle of the cone is such that the Mach number behind the shock . Results are presented for an oscillating cone for gas with , at different Mach numbers and semi cone angles. The Stiffness derivative decreases with pivot position and also with semi vertex angle, there is substantial change in the stiffness derivative when semi-vertex has been increased from 5 degrees to ten degrees, further increase in the semi-vertex angle results in marginal change in the stiffness derivative. Due the marginal change in the Mach number level there is marginal increase in the magnitude of the stability and with further increase in the inertia level the stability derivative conform to the Mach number independence principle. The present theory for Oscillating cone is restricted to quasi-steady case. Viscous effects have been neglected. The expressions so obtained for stability derivative in pitch are valid for a slender ogive which often approximates to the whole fuselage of an aircraft. Keywords: High Speed Flow, Hypersonic Flow, Oscillating cone, Stiffness derivative